GOVERNMENT MEASURES FOR CULTIVATING EMPOWERMENT IN THE TRANSGENDER COMMUNITY IN INDIA: AN OVERVIEW - Rasal, Pratibha Amrut; Dole, Vikas Suresh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study provides an overview of government measures aimed at fostering empowerment within the transgender community in India, based on secondary data analysis. The transgender community in India has long faced systemic marginalization and discrimination, hindering their access to basic rights and opportunities. In response to these challenges, the government of India has initiated various measures to address the needs and empower transgender individuals. Through a comprehensive review of secondary data sources, including government reports, academic studies, and NGO publications, this overview assesses the effectiveness and scope of government interventions. It examines key initiatives such as policy reforms, legal protections, social welfare programs, and educational initiatives tailored to the transgender community. Furthermore, it explores the challenges and gaps in the implementation of these measures, including societal attitudes, bureaucratic hurdles, and resource constraints. The analysis highlights the importance of inclusive policies and collaborative efforts between government agencies, civil society organizations, and transgender advocates to promote meaningful empowerment and inclusion. By shedding light on existing initiatives and areas for improvement, this overview contributes to ongoing discussions on enhancing the socio-economic and political rights of the transgender community in India.